Problem Solving: A Gateway to Valuation of the cultural diversity of migrant students (Praxis Educativa, 2023)
This essay exposes how migration to Chile impacts the enrollment of foreign students in educational establishments in the country. This event poses a challenge for teachers: to teach from an intercultural perspective that allows integrating the culture of migrant students during school learning. In this new and intercultural setting, the subject of mathematics through problem solving proposes an alternative to include characteristics of these students, such as their origin, history and culture. Therefore, it is necessary to work from a new approach the initial training of teachers of this specialty, which allows to have tools and knowledge that incorporate culture to the learning objectives of this subject, and to understand how from these activities it is possible to promote the inclusion and appreciation of cultural diversity in the classroom.
Keywords: Problem solving; initial teacher training; migrant; diversity; culture